Increasing awareness of food-choking and nutrition in children through education of caregivers: the CHOP community intervention trial study protocol - Lorenzoni, Giulia (BMC Public Health, 2019)
BACKGROUND: Choking is one of the leading causes of death among unintentional injuries in young children. Food choking represents a considerable public health burden, which might be reduced through increased effective preventative education programs. We present a protocol for a community intervention trial termed CHOP (CHOking Prevention project) that aimed to teach Italian families how to prevent food choking injuries and increase knowledge relating to nutrition. METHODS: Italian educational facilities were enrolled. Stratified randomization blocked by geographical area was performed. Each stratum was randomized to one of three different intervention strategies or to a control group. Educational intervention was delivered in the schools by experts and certified trainers as per the following three intervention strategies: directly to families (Strategy A); to teaching staff only, who subsequently delivered the same educational intervention to families (Strategy B); to health service staff only, who then delivered the educational intervention to teaching staff, who subsequently delivered the intervention to families (Strategy C). Participants completed a questionnaire about their knowledge on the topics presented during the educational interventions (pre-, post-, and follow-up of intervention). Information from the questionnaires was synthetized into 6 indicators in order to measure how effective each intervention strategy was. DISCUSSION: The issue of food choking injuries in children is relevant to public health. The protocol we present provides an opportunity to progress towards overcoming such challenges through a working model that can be implemented also in other countries. TRIAL REGISTRATION: ClinicalTrials.gov NCT03218618. The study was registered on 14 July 2017.